Anthropological analysis of skeletal material taken during rescue investigations at Plac Słowiański in Krakow (2017 season) - Marchewka, Justyna (Studia Ecologiae et Bioethicae, 2018)
The aim of the anthropological analysis was to estimate the Minimal Number of Individuals (MNI) in the examined ossuary taken during the rescue work at Plac Słowiański (Krakow). In addition, an attempt was made to determine the biological profile of the deceased and determine from which church cemeteries located near Plac Słowiański they could have originated. MNI was established based on preserved right temporal bones and amounted to 51. The most numerous bones in the examined material were skull bones and larger bones of the post-cranial skeleton. A significantly smaller proportion of children’s bones was also noted. Both of these observations jump on the bone selection that was made during the transfer of the skeletons of the primary graves to the secondary grave. The results of the research did not allow for an unequivocal indication of the origin of the remains, although it is more likely that the ossuary was created as a result of the transfer of bodies from the cemetery of the st. Krzyż Church.